BMI and BAI as Markers of Obesity in a Caucasian Population - Zwierzchowska, Anna (Obes Facts, 2013)
BACKGROUND: BMI is known to have limited accuracy, which is different for males and females with similar body fat content. That is why Bergman et al. (Obesity 2011;19:1083-1089) introduced an alternative variable of obesity, called the body adiposity index (BAI). Their primary research was conducted in samples of Mexican-American and African-American populations. The objective of our research was to investigate the sex-specific relationship between both BMI and BAI and body fat content in a healthy Caucasian population. The accuracy of both indexes was compared. METHODS: 684 women and 528 men aged 20-22 years with Caucasian origin only participated in the study. Participants were students of universities in southern Poland. They had no indication of cardiometabolic problems, as evaluated by interview. RESULTS: The study revealed that BAI is a more sensitive method in assessing obesity in Caucasian males rather than BMI. In the population of Caucasian women BAI results indicate a significant underestimation of obesity. CONCLUSION: The fact that there is a high statistical correlation between BAI and % fat mass among obese and overweight men and women suggests that BAI could be highly specific provided that the BAI cutoffs will be adapted to the European population.